Sarcopenia and sarcopenic obesity after cholecystectomy: A population‐based study. Issue 2 (28th December 2021) - Gan, Da; Wang, Xiaoyan; Xu, Xiaochen; Kang, Qingcong; Lu, Zhonghua; Jia, Menghan; Ru, Yuan; He, Xi; Mou, Yun; He, Wei; Zhu, Shankuan
Abstract: Objective: The present study aimed to investigate the associations of cholecystectomy with low muscle mass, low muscle strength, sarcopenia, and sarcopenic obesity. Methods: This population‐based study included data from 4, 909 participants aged 18 to 80 years. History of cholecystectomy was diagnosed using abdominal ultrasonography. Muscle mass was evaluated using a dual‐energy x‐ray absorptiometry scan, and muscle strength was evaluated using an electronic hand dynamometer. Sarcopenia was defined as the presence of both low muscle mass and low muscle strength. Sarcopenic obesity was defined as the presence of both sarcopenia and obesity. Multivariable logistic regression models were performed to investigate the associations of cholecystectomy with low muscle mass, low muscle strength, sarcopenia, and sarcopenic obesity. Results: Participants with history of cholecystectomy were more likely than those without to have low muscle mass, low muscle strength, and sarcopenia. Furthermore, compared with cholecystectomy that occurred within 7 years (7 years is the median interval between cholecystectomy and the physical examination), participants with cholecystectomy that occurred more than 7 years ago had higher odds of sarcopenia. Finally, whether obesity was defined by BMI or body fat percentage, cholecystectomy was positively associated with sarcopenic obesity. Conclusions: Cholecystectomy is associated with low muscle mass, low muscle strength, sarcopenia, and sarcopenic obesity.